A comparative study to determine the effectiveness of oral mifepristone and vaginal isosorbide mononitrate as cervical ripening agents for induction of labor in pregnant women with gestational age 28 to 34 weeks - Pandit, Meeta; Dave, Anupama; Thora, Akanksha; Dwivedi, Aparna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The process of inducing labor is definitely one of the most commonly done obstetric procedures worldwide. An unfavourable cervix is a major reason for unsuccessful induction. Cervix must be softened. IOL should only be performed when there is an obvious medical need and advantages are greater than risks. Methods: The present study was conducted at the Department of Obstetrics and Gynaecology, MGM Medical College, Indore from February 2023 to January 2024.One hundred pregnant women of gestational age 28 to 34 weeks, who had a valid indication for termination of pregnancy, were included in the study after valid consent and randomised into two groups. Oral Mifepristone was used in one group and vaginal isosorbide mononitrate IMN in the other. Modified Bishops Score was subsequently assessed and compared. Results: In the study, indications for termination were hypertensive disorders of pregnancy, IUFD, anhydramnios, severe oligohydramnios and PPROM. Mean±SD of Bishop score before and after IMN were 1.84±1.23 and 4.40±1.34, whereas for Mifepristone 1.42±1.42 and 4.92±1.68, respectively. Mean cervical ripening to delivery time in IMN group was 30.04±3.37 hours; while in mifepristone group, it was 28.50±3.48 hours. Most patients delivered vaginally in both the groups (IMN group 88%; mifepristone group 94%). Both Mifepristone and IMN were generally well-tolerated by participants. Conclusions: This study provides evidence supporting the effectiveness of both drugs as cervical ripening agents.